The Pharisees in Recent Catholic Writing - Swidler, Leonard J. (Horizons, 1983)
The negative image of the Pharisees in the Christian tradition since the time of the Gospels is stark, to say the least. Ninety percent of the references to them in elementary Catholic textbooks and seventy-eight percent in secondary Catholic school texts are negative. Because this image is historically unwarranted and because the Pharisees are the forefathers of present-day rabbinic Judaism, correcting that distorted image both in Christian scholarship and popular education is essential to further Jewish-Christian dialogue. With Vatican II there was "turning around" in the official Catholic Church on the image of the Pharisees, and since that time numerous official Catholic documents have called for a balancing of the distorted image of the Pharisees. Some Catholic scholars, mostly in the United States, and to some extent in Germany, have begun that scholarly and popular education process. John Pawlikowski, Eugene Fisher, Clemens Thoma, and Franz Mussner stand out in this work. But much remains to be done to bring that new scholarship into the classroom, books, and liturgy.